What Influence Does the AI Strategy Have on Possible Outcomes of Chinese Foreign Policy and Economic Development? - Wenning, Sebastian (Advances in Social Sciences Research Journal, 2023)
This article examines the impact of China's AI strategy on the country's economic development, digitalisation and geopolitical relations in both a domestic and international context. The analysis shows that China's AI strategy, especially the Next Generation Artificial Intelligence Development Plan, promotes AI education and research, leading to an increase in AI-related scientific publications and success in international AI competitions. This development may lead to a further strengthening of China's position in the global power structure to an almost disruptive shift in geopolitical bloc relations. Digitisation through AI technologies is also showing significant impact on the country's economy. Increased productivity and efficiency in various industries, especially in the automotive and electronics sectors, is leading to increased creative destruction in this regard. While millions of new jobs are being created in the AI sector, up to twelve percent of jobs in Chinese industry can be replaced by automation. The introduction of AI technologies generates higher economic output and productivity in some regions, as exemplified by the Pearl River Delta. Here, the AI clusters play a decisive role in regional economic development. Through these developments, China will rely less on imports and expand its economic presence by exporting AI-based products and services to numerous countries and industries. The new trade opportunities burgeoning in this way create opportunities for rapprochement, but growing competition and trade conflicts with other technologically advanced nations is also likely, as the controversial expansion of the Digital Silk Road and the Made in China 2025 initiative demonstrate.